Stigma and US Nurses’ Intentions to Provide the Standard of Maternal Care to Incarcerated Women, 2017 - Goshin, Lorie S. (Am J Public Health, 2020)
Objectives. To examine relationships among actionable drivers and facilitators of stigma and nurses’ intentions to provide the standard of maternal care recommended by the Association of Women’s Health, Obstetric, and Neonatal Nurses (AWHONN) for incarcerated women. Methods. We conducted a Web-based survey of perinatal nurses in the United States (n = 665; participation rate 98.0%; completion rate 95.3%) in July through September 2017. We used multivariable logistic regression to predict higher than median intentions to provide the standard of care. Results. Lower stigmatizing individual attitudes and institutional norms and higher perceived autonomy when caring for an incarcerated woman were significantly associated with higher care intentions. Knowledge of the AWHONN position statement on the standard of care or their own state’s shackling laws was not associated with higher care intentions. Conclusions. We documented significant associations among actionable drivers and facilitators of stigma and the intentions of a key health care provider group to deliver the standard of maternal care to incarcerated women. Individual- and institutional-level stigma-reduction interventions may increase the quality of maternal care and improve perinatal outcomes for women who give birth while incarcerated.